P347 New-onset autoimmune disorders, primarily psoriasis, in anti-TNF biologic exposed paediatric patients: the DEVELOP experience. (25th January 2019) - Veereman, G; Griffiths, A; Colletti, R; Gold, B; Izanec, J; Busse, C; Wang, Y; Escher, J
Abstract: Background: DEVELOP is a multi-centre, prospective, observational registry of the long-term safety and clinical outcomes of 6070 paediatric patients with inflammatory bowel disease (IBD) treated with anti-tumour necrosis factor biologics (aTNF) and/or other medical therapies for IBD as part of routine clinical care. DEVELOP has sites in the USA, Canada and the European Union. Our aim was to characterise the incidence of new autoimmune disorders (AD) in a paediatric IBD population exposed to aTNF compared with a population exposed only to non-biologics (NB). Methods: Physicians participating in the registry prescribe IBD treatments based on their usual clinical practice and standards of care. Pts are categorised into cohorts according to their prevalent or incident medication exposure, including patients receiving therapy prior to enrolment and/or during registry follow-up. The most recent available data cut (June 30 2018) includes 21083 patient-years (PY) of follow-up in the aTNF cohort and 11277 PY in the NB cohort. Investigators record all new AD in the study database during biannual visits. Results: Among all IBD patients, the incidence of all new AD was statistically significantly greater in the aTNF cohort (0.99 events/100 PY) than the NB cohort (0.27 events/100 PY) (Table 1). These results were driven by new-onset psoriasis (0.58 events/100 PY), the most frequently reported new AD in the aTNF cohort compared with 0.02 new psoriasis events/100 PY in the NB cohort. The incidence of serious new AD was low in both the aTNF cohort (0.20 events/100 PY) and the NB cohort (0.07 events/100 PY). In the aTNF cohort, serious new AD that occurred more than once included the following: psoriasis (0.06 events/100 PY, n = 12 events); sclerosing cholangitis (0.02 events/100 PY, n = 4); lupus-like syndrome (0.02 events/100 PY, n = 4); optic neuritis (0.01 events/100 PY, n = 3); autoimmune hepatitis (0.01 events/100 PY, n = 3). In the NB cohort, there were no reports of serious adverse events of psoriasis, optic neuritis, or lupus-like syndrome, and one report (0.01 events/100 PY) each of autoimmune hepatitis and juvenile idiopathic arthritis and two cases of sclerosing cholangitis (0.02 events/100 PY). Conclusions: New AD were noted approximately once every 100 PY in the aTNF cohort and were significantly more common compared with the NB cohort. New serious AD in the aTNF cohort were uncommon, with only 0.20 events per 100 PY. New AD do arise in aTNF treated paediatric IBD patients but overall are uncommon and not serious.